2021
DOI: 10.3390/antib10020012
|View full text |Cite
|
Sign up to set email alerts
|

New Autoantibody Specificities in Systemic Sclerosis and Very Early Systemic Sclerosis

Abstract: Chemokine (C-X-C motif) ligand 4 (CXCL4) is a biomarker of unfavorable prognosis in Systemic Sclerosis (SSc), a potentially severe autoimmune condition, characterized by vasculitis, fibrosis and interferon (IFN)-I-signature. We recently reported that autoantibodies to CXCL4 circulate in SSc patients and correlate with IFN-α. Here, we used shorter versions of CXCL4 and CXCL4-L1, the CXCL4 non-allelic variant, to search for autoantibodies exclusively reacting to one or the other CXCL4 form. Moreover, to address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…Recently, CXCL4 itself was found to behave as a self-antigen, maintaining a vicious cycle by promoting T1 IFN activation via pDCs and anti-CXCL4 antibodies by B cells, sustaining the SSc IFN signature [ 19 ]. Further work with CXCL4 has interestingly shown that the anti-CXCL4 antibodies were present in patients with VEDOSS (very early diagnosis of systemic sclerosis), suggesting that this mechanism can intervene very early in the pathogenesis of disease, before clinically apparent tissue damage [ 20 ].…”
Section: From Danger Sensors To Interferon-stimulated Genes: a Multif...mentioning
confidence: 99%
“…Recently, CXCL4 itself was found to behave as a self-antigen, maintaining a vicious cycle by promoting T1 IFN activation via pDCs and anti-CXCL4 antibodies by B cells, sustaining the SSc IFN signature [ 19 ]. Further work with CXCL4 has interestingly shown that the anti-CXCL4 antibodies were present in patients with VEDOSS (very early diagnosis of systemic sclerosis), suggesting that this mechanism can intervene very early in the pathogenesis of disease, before clinically apparent tissue damage [ 20 ].…”
Section: From Danger Sensors To Interferon-stimulated Genes: a Multif...mentioning
confidence: 99%
“…Importantly, CXCL4 and IFN-I are closely linked via the process of triggering the nucleic sensor TLRs that leads to the IFN-I signature. In addition to that, we have previously shown that CXCL4 also acts as B-cell autoantigen in SSc patients [ 11 , 12 ]. This could be the result of formation of large CXCL4-DNA complexes in SSc patients, which could contribute to the immunogenicity of CXCL4.…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, we have previously shown that CXCL4-DNA complexes circulate in SSc patients, correlate with IFN-I and are also present in SSc-affected skin where they co-localize with an IFN-I induced gene [ 5 ]. Anti-CXCL4 antibodies were higher in patients with pulmonary fibrosis and digital ulcers and were associated with disease activity [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations